Anais Dos Workshops Do VI Congresso Brasileiro De Informática Na Educação (CBIE 2017) 2017
DOI: 10.5753/cbie.wcbie.2017.1202
|View full text |Cite
|
Sign up to set email alerts
|

Análise automatizada do discurso de aprendizes de programação: relações entre emoções e nível de experiência

Abstract: Abstract. Techniques related to Multimodal Learning Analytics may be useful to evaluate the previous level of expertise of students engaged in learning IntroduçãoCom a chegada da era digital começou a se pensar em quais habilidades seriam necessárias para os alunos que iriam fazer parte dessa sociedade futuramente. Dentre as habilidades relevantes para o século 21 destacam-se o pensamento crítico, capacidade de solução de problemas complexos, criatividade, comunicação eficiente e alta produtividade. Face a ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…The analyses are based on statistical techniques such as the mean, median, standard deviation, histograms, and hierarchical clustering. More specifically, the studies of [16], [25], [26] that analyze data generated by the Dr. Scratch tool from artifacts available in the Scratch online community have limited results due to the use of the duplicate code, employment of bad programming practices and the various nature of the files (stories, animations and games) as shown by [10], [27], [28]. In addition, the analysis of artifacts indicates their complexity, i.e., it has limitations in the process of measuring the acquisition of Computational Thinking.…”
Section: Data Mining Framework To Analyze the Evolution Of Computational Thinking Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analyses are based on statistical techniques such as the mean, median, standard deviation, histograms, and hierarchical clustering. More specifically, the studies of [16], [25], [26] that analyze data generated by the Dr. Scratch tool from artifacts available in the Scratch online community have limited results due to the use of the duplicate code, employment of bad programming practices and the various nature of the files (stories, animations and games) as shown by [10], [27], [28]. In addition, the analysis of artifacts indicates their complexity, i.e., it has limitations in the process of measuring the acquisition of Computational Thinking.…”
Section: Data Mining Framework To Analyze the Evolution Of Computational Thinking Skillsmentioning
confidence: 99%
“…In addition, the analysis of artifacts indicates their complexity, i.e., it has limitations in the process of measuring the acquisition of Computational Thinking. The authors indicated as possible causes the following problems in the proposal of the workshop: activities of increasing complexity, an educational rubric structure and the long term [10], [27], [28].…”
Section: Data Mining Framework To Analyze the Evolution Of Computational Thinking Skillsmentioning
confidence: 99%